2018
DOI: 10.1037/xlm0000466
|View full text |Cite
|
Sign up to set email alerts
|

Sequential whole report accesses different states in visual working memory.

Abstract: Working memory (WM) enables a rapid access to a limited number of items that are no longer physically present. WM studies usually involve the encoding and retention of multiple items, while probing a single item only. Hence, little is known about how well multiple items can be reported from WM. Here we asked participants to successively report each of up to 8 encoded Gabor patches from WM. Recall order was externally cued, and stimulus orientations had to be reproduced on a continuous dimension. Participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 63 publications
4
23
1
Order By: Relevance
“…The current results replicated the findings from our previous study (Peters et al, 2018) by showing a discontinuous decrease of response precision, measured as the width of the response error distribution (inverted s.d.). That is, we observed a steep drop from the first to the second report and only a slight continuous decrease thereafter (Figure 1b, 1c).…”
Section: Response Precision Decreases Discontinuously Across the Reposupporting
confidence: 91%
See 4 more Smart Citations
“…The current results replicated the findings from our previous study (Peters et al, 2018) by showing a discontinuous decrease of response precision, measured as the width of the response error distribution (inverted s.d.). That is, we observed a steep drop from the first to the second report and only a slight continuous decrease thereafter (Figure 1b, 1c).…”
Section: Response Precision Decreases Discontinuously Across the Reposupporting
confidence: 91%
“…Given the importance of interference for the distinction between high versus low memory quality storage, we sought to characterize in detail the interference processes that are responsible for the transfer of items from the first to the second state in working memory. In our previous study (Peters et al, 2018) we showed in two experiments that the steep drop in response precision from the first to the second report was due to the executive interference. Specifically, we have implemented executive interference by asking participants to orient a Gabor probe vertically (Experiment 3) or to change the color of a patch to blue (Experiment 4) during the retention period before first report.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations